If it's not what You are looking for type in the equation solver your own equation and let us solve it.
n/6+3=-2
We move all terms to the left:
n/6+3-(-2)=0
We add all the numbers together, and all the variables
n/6+5=0
We multiply all the terms by the denominator
n+5*6=0
We add all the numbers together, and all the variables
n+30=0
We move all terms containing n to the left, all other terms to the right
n=-30
| .5x–1.0675=3x–4.145. | | 13x+1=5–x | | (2x+8)=−16 | | h/3+12=19 | | h/2+9=19 | | F(x)=(5x²-3)(x²+x+4) | | x+(x-20)=68 | | 4x/2+5/2=3 | | (x-20)+x=68 | | 7(x+3)=5x-8 | | -9+8a=15 | | 3y+3=12× | | 60x+840=300 | | 4c(1-c)=8 | | 60x+300=840 | | 0,5x+0,5=6 | | 840x+300=60 | | 60x-300=840 | | 8/3x*1/3x=131/3+7/3x | | 17-4x=0 | | 3+5)*2y=(5*8)-(2*4) | | 4/x=5/45 | | -10.74=x-(-11) | | 159=29+x+x | | 159=29+x-x | | 75m+52,525=55,550-175M | | 7/3x+1/3x=1+3/5x | | 175m-75m+52,525=55,550-175 | | 3-7=x+3 | | -12+5x=5(x-2) | | 4(z-1)=2(z+2) | | x2-61x+900=0 |